Sensitive detection of formamidopyrimidine-DNA glycosylase activity based on target-induced self-primed rolling circle amplification and magnetic nanoprobes. Issue 7 (8th March 2018) - Song, Juan; Yin, Fei; Li, Xia; Dong, Na; Zhu, Yingjie; Shao, Yanan; Chen, Baoli; Jiang, Wei; Li, Chen-zhong
Abstract : We developed a novel approach to sensitive detection of formamidopyrimidine-DNA glycosylase activity based on target-induced selfprimed rolling circle amplification and magnetic nanoprobes. Abstract : We developed a novel approach to determine formamidopyrimidine DNA glycosylase (FPG) activity by taking advantage of target-induced self-primed rolling circle amplification (RCA) and magnetic nanoprobes. Herein, a unique nick (8-oxoguanine, 8-oxoG) was positioned in duplex DNA containing P-circle and P1, which together serve as a FPG substrate, RCA template, and RCA primer probe. The presence of FPG specifically binds 8-oxoG and cleaves the P-circle into two parts, producing 5′-phosphoryl termini. A phosphodiester bond between the 5′-phosphoryl and 3′-hydroxyl termini was formed with the addition of T4 DNA ligase, producing an unnicked circular strand. Using the unnicked strand as the RCA template, the P1 hybridized with the circle probe as a primer will trigger the RCA process. The RCA reaction produces amounts of long tandem-repeat DNA tiles with multiple recognizing regions for the FAM modified DNA probes (FP) and biotin-modified DNA probes (BP). With the streptavidin–biotin interaction, the BPs and FPs can be easily immobilized on the surface of streptavidin-modified magnetic microbeads (MBs). Due to the RCA enhanced and highly-concentrated fluorescence accumulation on the MBs, an ultralow detection limit of 1.033 U mL −1 for FPG was obtained. Combined with the high tolerance capability of human blood serum owing to magnetic isolation, the FPG assays in human blood serum were also obtained using fluorescence and confocal laser scanning microscopy. These results indicate that this robust self-primed RCA combined with magnetic nanoprobes is an excellent candidate for quantitatively monitoring the FPG activity responsible for DNA oxidative damage-related clinical diagnosis and therapy.